1995
DOI: 10.1038/bjc.1995.392
|View full text |Cite
|
Sign up to set email alerts
|

Increased sensitivity to the prodrug 5'-deoxy-5-fluorouridine and modulation of 5-fluoro-2'-deoxyuridine sensitivity in MCF-7 cells transfected with thymidine phosphorylase

Abstract: Summary Platelet-derived endothelial cell growth factor (PD-ECGF) is identical to human thymidine phosphorylase (dThdPase). The human MCF-7 breast cancer cell line was transfected with the dThdPase cDNA and expressed a 45 kDa protein that was detected with anti-dThdPase antibody. Cell lysates possessed elevated dThdPase activity and cells had up to 165-fold increased sensitivity to the prodrug 5'-deoxy-5-fluorouridine (5'-DFUR) in vitro. Sensitivity to 5-fluorouracil (5-FU) and 5-fluoro-2'-deoxyuridine (5-FUdR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
80
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 8 publications
8
80
2
Order By: Relevance
“…Using strong virus promoters, it has been reported that the 5-FU derived from 5 0 -DFUR can diffuse from the transfected cancer cells to exert bystander killing effect on their neighbour cells in a gap junction-independent manner (Patterson et al, 1995;Kato et al, 1997). In this study, we also compared the bystander effect of pFBD/KCT-and pcDNA3/TP-transfected cancer cell lines.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Using strong virus promoters, it has been reported that the 5-FU derived from 5 0 -DFUR can diffuse from the transfected cancer cells to exert bystander killing effect on their neighbour cells in a gap junction-independent manner (Patterson et al, 1995;Kato et al, 1997). In this study, we also compared the bystander effect of pFBD/KCT-and pcDNA3/TP-transfected cancer cell lines.…”
Section: Discussionmentioning
confidence: 96%
“…Low transfection rate is still one of the major barriers for the success of cancer GDEPT in the clinic. It has been reported that the small portion of CMV promoter-driven TP-transfected cells can effectively convert 5 0 -DFUR into 5-FU, which can be released and performed cytotoxic effect onto the neighbouring cells (bystander effect) (Patterson et al, 1995). Figure 5C and D show that when pcDNA3-TP-or pFBD/KCT-transfected RKO or H630 cells composed only 5% of the whole-cell population, the sensitivity of H630 and RKO cell lines to 5 0 -DFUR was significantly enhanced.…”
Section: The Bystander Effect Of Pfastbacdualdpromoter/jb4-cea205-tp-mentioning
confidence: 99%
See 1 more Smart Citation
“…Not only did TP promote endothelial cell migration, but cancer cells overexpressing the factor had a significantly faster growth rate . TP enzyme activity is also essential for the metabolism of fluoropyrimidines, which suggests that TP-overexpressing tumours may be sensitive to antimetabolite chemotherapy (Patterson et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…TP has been shown to exhibit a chemotactic and mitogenic capacity on endothelial cells in several angiogenic model systems, and its expression in human breast cancer cells has been shown to correlate with microvessel density in some studies (Fajardo et al, 1992;Folkman, 1996;Fox et al, 1996). Moreover, TP expression is 260-fold higher in invasive bladder cancer (O'Brien et al, 1995) and 27-fold higher in invasive breast carcinoma than normal tissue (Patterson et al, 1995). In ovarian carcinomas, areas of increased expression of TP have been associated with high blood velocity as measured by colour Doppler imaging (Reynolds et al, 1994).…”
mentioning
confidence: 99%